2010
DOI: 10.1371/journal.pone.0012821
|View full text |Cite
|
Sign up to set email alerts
|

Pkd1 and Pkd2 Are Required for Normal Placental Development

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is a common cause of inherited renal failure that results from mutations in PKD1 and PKD2. The disorder is characterized by focal cyst formation that involves somatic mutation of the wild type allele in a large fraction of cysts. Consistent with a two-hit mechanism, mice that are homozygous for inactivating mutations of either Pkd1 or Pkd2 develop cystic kidneys, edema and hemorrhage and typically die in midgestation. Cystic kidney disease is unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 49 publications
4
56
0
2
Order By: Relevance
“…These findings support the observed endothelial dysfunction and reduced nitric oxide generation in ADPKD patients, as well as an increased contractile response of the arterial vasculature in Pkd2 +/-mice (34). A more recent study, in addition, showed that polycystins play a complex role in the maintenance of vascular integrity and that Pkd1 and Pkd2 are necessary for the normal development of the placenta in mice (35).…”
Section: Cellular and Transport Abnormalitiessupporting
confidence: 82%
“…These findings support the observed endothelial dysfunction and reduced nitric oxide generation in ADPKD patients, as well as an increased contractile response of the arterial vasculature in Pkd2 +/-mice (34). A more recent study, in addition, showed that polycystins play a complex role in the maintenance of vascular integrity and that Pkd1 and Pkd2 are necessary for the normal development of the placenta in mice (35).…”
Section: Cellular and Transport Abnormalitiessupporting
confidence: 82%
“…We detected a similar defect, albeit milder, in embryos with selective endothelial cell deletion of Pkd2 (Pkd2 cond/cond ; Tie2-Cre + aka Pkd2 endo- ) (Figure 5C, 5G-5I). We have previously demonstrated that Tie2-Cre mediated deletion of Pkd1 or Pkd2 in endothelial cells only partially recapitulates the vascular phenotype observed in null animals (Garcia-Gonzalez et al, 2010). Specifically, Pkd2 endo- embryos lack detectable edema and when we analyzed the lymphatic vessels in these mice at E14.5, we found no difference in comparison to controls (Figure S5).…”
Section: Resultsmentioning
confidence: 97%
“…hemorrhage) or cardiac failure. Studies by our group, however, suggest that placental insufficiency is the predominant factor responsible for this outcome (Garcia-Gonzalez et al, 2010). Similar to homozygous mice, humans with homozygous incompletely penetrant mutations may present with massive PKD in utero (Vujic et al, 2010).…”
Section: Polycystic Kidney Diseases (Pkd)mentioning
confidence: 83%